Triglyceride-glucose index as a prognostic indicator in advanced gastric cancer: Insights and future research - Zhao, Cheng-Fei; Liu, Xiao-Ling; Wu, Ning-Bi; Xu, Zhi-Feng (World journal of gastroenterology : WJG, 2025)
Gastric cancer (GC), the fifth most common malignancy worldwide, poses a substantial challenge in clinical oncology, particularly in its advanced stages. Despite advancements in immunotherapy, patient prognosis remains poor, underscoring the need for reliable prognostic tools to refine treatment strategies. A study by Yao et al explores the role of the triglyceride-glucose (TyG) index as a prognostic marker for advanced GC patients receiving immunotherapy combined with chemotherapy. The results of the study demonstrate that the TyG index correlates with improved survival outcomes, including better progression-free survival and overall survival. This editorial critically evaluates the significance of these findings, discusses their implications for future research, and highlights innovative directions that could drive further breakthroughs in the application of the TyG index to cancer therapy. This editorial also highlights the potential of TyG in advancing precision oncology and advocates for global validation and mechanistic investigations to further solidify its clinical utility. Future research should focus on validating the TyG index across various malignancies, exploring its potential to influence immunotherapy through metabolic interventions, and developing multi-biomarker models that integrate TyG with immune and genomic profiles.